The non bis in idem principle in the disciplinary rules of the attorneys that work with the State - Corredor-Ramírez, Andrea Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article is aimed at students and lawyers, in order to do a conscious exercise of the profession in front of the consequences that mainly in disciplinary matters framed our actions, not only as lawyers, but also those who in turn boast the quality of Civil servants. Its purpose is to establish if there is an infringementof the principle of non bis in idem applying the disciplinary rules of the lawyer and the Civil servant to a professional of the law that exerts public function as the attorney to the service of the State, so it is necessary to establish the types of bonding of the attorney with the Administration, disciplinary rules for lawyers and Civil servants and finally compare the latter from the principle of non bis in idem to determine whether or not there is infringement.